2010
DOI: 10.2118/112500-pa
|View full text |Cite
|
Sign up to set email alerts
|

A New Laboratory Method for Evaluation of Sulfate Scaling Parameters from Pressure Measurements

Abstract: Sulfate scaling in offshore waterflood projects, in which sulfate from the injected seawater (SW) reacts with metals from the formation water (FW), forming salt deposit that reduces permeability and well productivity, is a well known phenomenon. Its reliable prediction is based on mathematical models with well-known parameters.Previous research presents methods for laboratory determination of model coefficients using breakthrough concentration during coreflooding. The concentration measurements are complex and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Yassin (2007, 2009) reported that increasing temperature, pressure head, and brine concentration had an unfavorable impact on the permeability reduction and reaction rate constant. Clarifying the constant for each model of scale deposition, more accurate for artificial cores than for natural reservoir cores based on a series of core flooding tests dependent on pressure measurements, was done by Carageorgos et al (2010). Figuring the interaction between reservoir lithology and a scale inhibitor has recently turned into researchers' interest like Todd (2012), who did some tests within modern phosphorus inhibitors that have some advantages in comparison with the conventional types.…”
Section: Introductionmentioning
confidence: 99%
“…Yassin (2007, 2009) reported that increasing temperature, pressure head, and brine concentration had an unfavorable impact on the permeability reduction and reaction rate constant. Clarifying the constant for each model of scale deposition, more accurate for artificial cores than for natural reservoir cores based on a series of core flooding tests dependent on pressure measurements, was done by Carageorgos et al (2010). Figuring the interaction between reservoir lithology and a scale inhibitor has recently turned into researchers' interest like Todd (2012), who did some tests within modern phosphorus inhibitors that have some advantages in comparison with the conventional types.…”
Section: Introductionmentioning
confidence: 99%
“…These results were confirmed by a similar following study performed by Merdhah and Yassin using Berea sandstone cores. Utilization of pressure measurements through a novel methodology was reported by Carageorgos et al to determine scale deposition coefficients in coreflooding experiments. The proposed calculation methodology was found to be more precise for the artificial cores, compared to the natural reservoir cores.…”
Section: Introductionmentioning
confidence: 99%
“…Amount of the parameter is the same in both of the Moghadasi et al (2004) experiments. This is because of the same pore space properties in these experiments (Carageorgos et al 2010). The low velocity in the first experiment of Moghadasi et al (2004) performs bridging of particles that results in the higher rate of the particles capturing ( 0 ) in (16) Fig.…”
Section: Dbf Model Verification With Experimental Datamentioning
confidence: 88%